High gene flow and complex treeline dynamics of Larix Mill. stands on the Taymyr Peninsula (north-central Siberia) revealed by nuclear microsatellites - Kruse, Stefan (Dr.); Epp, Laura Saskia; Wieczorek, Mareike; Pestryakova, Luidmila A. (Prof. Dr.); Stoof-Leichsenring, Kathleen R. (Dr.); Herzschuh, Ulrike (Prof. Dr.) (Tree Genetics & Genomes, 2018)
Arctic treelines are facing a strong temperature increase as a result of recent global warming, causing possible changes in forest extent, which will alter vegetation-climate feedbacks. However, the mode and strength of the response is rather unclear, as potential changes are happening in areas that are very remote and difficult to access, and empirical data are still largely lacking. Here, we assessed the current population structure and genetic differentiation of Larix Mill. tree stands within the northernmost latitudinal treeline reaching ~ 72° N in the southern lowlands of the Taymyr Peninsula (~ 100° E). We sampled 743 individuals belonging to different height classes (seedlings, saplings, trees) at 11 locations along a gradient from ‘single tree’ tundra over ‘forest line’ to ‘dense forest’ stands and conducted investigations applying eight highly polymorphic nuclear microsatellites. Results suggest a high diversity within sub-populations (HE = 0.826–0.893), coupled, however, with heterozygote deficits in all sub-populations, but pronounced in ‘forest line’ stands. Overall, genetic differentiation of sub-populations is low (FST = 0.005), indicating a region-wide high gene flow, although ‘forest line’ stands harbour few rare and private alleles, likely indicating greater local reproduction. ‘Single tree’ stands, located beyond the northern forest line, are currently not involved in treeline expansion, but show signs of a long-term refuge, namely asexual reproduction and change of growth-form from erect to creeping growth, possibly having persisted for thousands of years. The lack of differentiation between the sub-populations points to a sufficiently high dispersal potential, and thus a rapid northward migration of the Siberian arctic treeline under recent global warming seems potentially unconstrained, but observations show it to be unexpectedly slow.